2014
DOI: 10.1016/j.jobcr.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Dental fluorosis and periodontium: A game of shadows?

Abstract: a b s t r a c tDental fluorosis is a condition which is said to be present when the morphologic features of a tooth are altered clinically, in the form of discoloration or anatomic malformation which is attributed to the developmental changes induced by excess fluoride levels in plasma at the time of tooth formation. In India, an estimated 60 million people are at risk and 6 million people are disabled due to fluorosis. Lack of understanding into the effects of fluorosis on periodontium has left a blind spot i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Vandana et al reported that there is a strong association of occurrence of periodontal disease and dental fluorosis [ 48 ]. The more serious dental fluorosis is, the rougher the tooth surface is, which makes periodontal bacteria easier to colonize on the tooth surface and difficult for scaling and root planning and may promote the occurrence of periodontal disease [ 49 ]. Treponema lecithinolyticum is a dominant specie related to the incidence of periodontitis [ 50 ]; our study also showed a relative high abundance of Treponema lecithinolyticum in the DF group compared with the HC group, suggesting that there may be a potentially high risk of periodontitis in the dental fluorosis population.…”
Section: Discussionmentioning
confidence: 99%
“…Vandana et al reported that there is a strong association of occurrence of periodontal disease and dental fluorosis [ 48 ]. The more serious dental fluorosis is, the rougher the tooth surface is, which makes periodontal bacteria easier to colonize on the tooth surface and difficult for scaling and root planning and may promote the occurrence of periodontal disease [ 49 ]. Treponema lecithinolyticum is a dominant specie related to the incidence of periodontitis [ 50 ]; our study also showed a relative high abundance of Treponema lecithinolyticum in the DF group compared with the HC group, suggesting that there may be a potentially high risk of periodontitis in the dental fluorosis population.…”
Section: Discussionmentioning
confidence: 99%
“…The role of some of the etiological factors of periodontal disease such as age, gender, ethnicity, socio-economic status, lifestyle, smoking and oral hygiene has been studied in some populations in India 24 , 25 but the effect of fluoride on periodontal tissue remains controversial, even though its association with tooth decay is well established. 26 The epidemiological data regarding the periodontal status of individuals living in areas with highly fluoridated water are inconsistent. As regards malocclusion, few recent investigations have analyzed and classified dental occlusion in school populations in northern Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Authors have reported no association between periodontal parameters and fluorosis, 30,31 increased periodontal scores, 5,7 and reduced periodontal scores. 24,32,33 Recently, a review 34,35 has discussed about various detrimental effects of fluoride on periodontal structures. Going by molecular aspect as well, the excess of fluoride in water can not only influence the microbial flora but the influence of this (possibly) altered microbial flora on the already altered/modified oral tissues remains to be studied.…”
mentioning
confidence: 99%